Seroprevalence and Risk Factors for Toxoplasma gondii Infection in Goats in Southern Brazil - Moura, Anderson Barbosa de; Ribeiro, André; Souza, Antonio Pereira de; Silva, Marcio Orides da; Machado, Gustavo; Klauck, Vanderlei; Pazinato, Rafael; Silva, Aleksandro Schafer Da (Acta Scientiae Veterinariae, 2016)
Background: Toxoplasma gondii is a coccidium, obligate intracellular protozoan, with complex life cycle, affecting virtually all-animal species homoeothermics. Goats are considered susceptible to infection by T. gondii, alterations being reported as pathological fetal death (with subsequent reabsorption), abortion, mummification, and/or the birth of weak goats. Because of these consequences to the animal, the disease is investigated throughout the Brazilian territory. Therefore, the aim of this study was to estimate the seroprevalence of Toxoplasma gondii antibodies and identify risk factors in goats. Materials, Methods & Results: It were collected 654 blood samples from goats distributed on west and mountainous regions of Santa Catarina, Brazil. The number municipalities with the highest numbers of goats were used, with an expected prevalence of 25%, error of 3.2% and confidence level of 95%. All collected samples were tested by indirect immunofluorescence assay (IFA), and 216 (33.02%; 95% CI 29.43-36.77) had antibodies against T. gondii (IFA ≥ 1: 64). Titration 1:64 was observed more frequently (60.2%; 130/216) among seropositive animals. The region with the highest prevalence was the west, i.e., more prone to infections present, with 1.16 more chances than the mountainous region. Animals Boer were more likely to T. gondii infection, being race is a risk factor for disease. When the presence of cats on the property, and these animals had chances of direct contact with cats, the chance of infection increased significantly, being 1.04 times higher went compared with lack of this feature. Regarding age, the animals aged two to five years had higher seropositivity (77.8%). Statistical analysis of effect-cause studies reported a relationship between soropositive animals and neurological problems (P ≤ 0.05), but no relation was found for T. gondii infection and reproductive problems (P > 0.05). Discussion: In the state of Santa Catarina, approximately 33% of the goats were seropositive for T. gondii, according to results of this study. Several other studies has been performed on T. gondii antibodies detection in Brazil, such as Paraná which was 44.68%, in Rio Grande do Norte was 17.1%, in Rio de Janeiro was 29.12%, in Maranhão was 36.95%, in Bahia was 17.4%, in Minas Gerais was 21.4%, in Alagoas was 39% and in Rio Grande do Sul was 30%. The type of food and water source given to the animals was not considered a risk factor for T. gondii infection, although some authors mention that cat feces contaminated with oocysts of the parasite can be more easily ingested in the diet with concentrated (cats have access) and natural water sources. This study showed that 53% of the animals studied had contact with cats, and this variable was considered a risk factor for disease. Statistically, unverified relationship between reproductive problems and goats seropositive for T. gondii, although of approximately 24% of the animals studied showed some reproductive problems (abortion, mummified or heat repetition). In the effect-cause analysis, neurological issues were related to infection by T. gondii in goats, the that can easily be explained because the parasitic cysts of T. gondii may persist in the central nervous system for a long period. The results suggest that infection by T. gondii occurs in goats in two regions of Santa Catarina, in addition, and the risk factors related to disease was between both studied regions, race and presence and contact with cats, just as there is a relation between disease and neurological disorders in goats.